Mental health implications of lockdown during corona virus pandemic among adults resident in Ibadan, Nigeria (2020)
The study examined the mental health implications of lockdown during coronavirus pandemic among adult residents in Ibadan, Nigeria. Descriptive survey research method was adopted for the study. The study made use of questionnaire adapted from the General Health Questionnaire (GHQ-12) and GHQ- 28. One hundred and thirty-two respondents filled the validated questionnaire with a reliability co- efficient of 82 at 0.05 level of significance. Three research questions and one hypothesis were formulated for the study. Findings revealed that there is a high level of effect of lockdown during coronavirus (COVID-19) pandemic on the anxiety level among adults resident in Ibadan. On the whole, sleeplessness is perceived as the dominant of two variables and is significantly positively correlated with depression and anxiety with the least coefficient (r= 0.434**) is also significant and positively correlated with depression among adult residents in Ibadan. Based on these findings, the government at all levels (Local, State and Federal) should provide adequate palliative measures for their citizens bearing in mind that with the lockdown, individual’ would not have adequate income. The Social Workers should also organize virtual meetings and trainings to educate these adults on coping mechanisms during this lockdown period.